1998
DOI: 10.1002/(sici)1521-1878(199801)20:1<30::aid-bies6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Silent chromatin in yeast: an orchestrated medley featuring Sir3p

Abstract: Extensive regions of chromosomes can be transcriptionally repressed through silencing mechanisms mediated by complex chromatin structures. One of the most refined molecular portraits of silenced chromatin comes from studies of the silent mating‐type loci and telomeres of S. cerevisiae. In this budding yeast, the Sir3p silent information regulator emerges as a critically important silencing component that interacts with nucleosomes and other silencing proteins. Not only is it essential for silencing, but Sir3p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…If SIR proteins can spread along chromatin, then what stops the complex from entering genomic regions that need to stay active? Clearly, overall SIR protein concentrations determine how far silencing spreads (Stone and Pillus, 1998). In addition, the HAT Sas2 and the acetylhistone binding Bdf1 bromodomains buffer euchromatin and maintain it transcriptionally active through H4 Lys16 acetylation (Kimura et al, 2002;Ladurner et al, 2003;Suka et al, 2002).…”
Section: Sir2 Metabolites Regulate the Sir Silencing Complexmentioning
confidence: 99%
“…If SIR proteins can spread along chromatin, then what stops the complex from entering genomic regions that need to stay active? Clearly, overall SIR protein concentrations determine how far silencing spreads (Stone and Pillus, 1998). In addition, the HAT Sas2 and the acetylhistone binding Bdf1 bromodomains buffer euchromatin and maintain it transcriptionally active through H4 Lys16 acetylation (Kimura et al, 2002;Ladurner et al, 2003;Suka et al, 2002).…”
Section: Sir2 Metabolites Regulate the Sir Silencing Complexmentioning
confidence: 99%
“…As a complement to these findings, histone colleagues (168) showed that in duck erythroblasts nascent H4 was found in un-, mono-, and dimodified deacetylation has been mechanistically tied to gene repression, as evidenced by transcriptional silencing isoforms, the latter described as a simultaneously monoacetylated/monophosphorylated species. It was in yeast (24,188), and by the recruitment of histone deacetylase (HDAC) by factors such as the repressor also observed that 20 min after chromatin assembly, at least 50% of the new H4 was present in the un-Rb (26, 128,131) and the methyl-CpG-binding protein MeCP2 (96,146,221). The involvement of dynamic modified form, demonstrating acetate and/or phosphate turnover.…”
Section: Annunziato and Hansenmentioning
confidence: 99%
“…The existence of local concentrations of specific proteins has been proposed to compartmentalize chromatin regions, creating an index system for the nucleus (Gasser and Laemmli, 1987;Stone and Pillus, 1998). The local concentration of specific proteins, such as Hp1␣ and -␤, could also be critical for defining domains that should be repressed.…”
Section: Hp1␣ and -␤ Are Maintained Through Dna Replicationmentioning
confidence: 99%